2018
DOI: 10.4103/picr.picr_159_16
|View full text |Cite
|
Sign up to set email alerts
|

Payment for participation in clinical research: Review of proposals submitted to the ethics committees

Abstract: Objective:In view of dearth of information in national and international guidelines on payment practices in research, the present study was done to find out payments for participation allowed by 3 Ethics committees (ECs) and reasons for payment.Method:This was a retrospective observational study which analysed research proposals reviewed by 2 institutional and 1 non-institutional ECs over a period of 2 years. The permission of ECs was obtained and confidentiality of data was maintained.Results:Of the 73 studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Consistent with previous research, the wide variation of payments within biomedical and sociobehavioral studies suggests that payment decisions are relatively unstructured in both types of studies, which is expected given the dearth of institutional and regulatory guidance on payments to research participants (Bernstein & Feldman, 2015;Grady et al, 2005;Henderson, 2015;. Still, our findings suggest that researchers' payment decisions are influenced by the type of research (e.g., quantitative, qualitative, or mixed), the amount of time that participation requires, the amount of risk that participation entails, and the number of interactions between participants and researchers, rather than whether the research was biomedical or sociobehavioral, which is consistent with previous research (Fry et al, 2005;Grady et al, 2005;Marathe et al, 2018;Ripley et al, 2010a). The present study is also consistent with previous research that suggests that biomedical studies typically pay more than sociobehavioral studies and that such differences may be due to greater risk in biomedical studies, which our study also showed (Grady et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research, the wide variation of payments within biomedical and sociobehavioral studies suggests that payment decisions are relatively unstructured in both types of studies, which is expected given the dearth of institutional and regulatory guidance on payments to research participants (Bernstein & Feldman, 2015;Grady et al, 2005;Henderson, 2015;. Still, our findings suggest that researchers' payment decisions are influenced by the type of research (e.g., quantitative, qualitative, or mixed), the amount of time that participation requires, the amount of risk that participation entails, and the number of interactions between participants and researchers, rather than whether the research was biomedical or sociobehavioral, which is consistent with previous research (Fry et al, 2005;Grady et al, 2005;Marathe et al, 2018;Ripley et al, 2010a). The present study is also consistent with previous research that suggests that biomedical studies typically pay more than sociobehavioral studies and that such differences may be due to greater risk in biomedical studies, which our study also showed (Grady et al, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…28 Moreover, the Chilean healthcare system provides meaningful access to health services, 29 so that potential participants' clinical needs can reasonably be met outside the research context. And the financial compensation that potential participants might obtain by enrolling in research is typically small and limited to reimbursements for time or expenses incurred-particularly in phase 3/4 trials, 30 which declined most sharply after Law 20.850 was introduced. Thus, it seems unlikely that the law made potential participants noticeably worse-off.…”
Section: Research Participantsmentioning
confidence: 99%
“…The relatively low amounts of payment may be related to the university context in which the studies were conducted, where research is typically initiated by the primary investigator rather than other entities. For example, Marathe et al (2018) found that studies initiated by investigators paid less than studies initiated by pharmaceutical companies or governments and suggested that budgetary constraints and investigator's perception of risks were likely the reasons for low payments in those studies. Therefore, budgetary constraints and investigators' perceptions of relatively low risk may have also contributed to low payment amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers may choose to pay participants for various reasons (Gelinas et al, 2018), such as to bolster recruitment efforts (Bentley & Thacker, 2004; Ripley, Macrina, Markowitz, & Gennings, 2010b), compensate for study-related costs, time, and inconvenience (Fry et al, 2005; Mweemba, Ali, & Hyder, 2018), and as a way to show appreciation for participants’ contributions (Resnik, 2015). Research shows that amounts and forms of payment for research participation vary widely (Fry et al, 2005; Latterman & Merz, 2001; Marathe et al, 2018). Some research also shows that payment amounts depend on the research setting, the amount of time that research participation requires, the procedures that participants will experience, and the type of research (e.g., early phase clinical experiments vs. late-phase clinical trials or biomedical vs. sociobehavioral research) (Fry et al, 2005; Marathe et al, 2018; Mweemba et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation